Konsep Musyarakah Dalam Pandangan Said Nursi - Mahfud (Journal Khafi : Journal Of Islamic Studies, 2023)
Musyarakah as a product based on partnership, if it is to be successful, its implementation must rely on healthy competition and prevent abuse of dominant positions in business partnerships, and the most important thing is to overcome any problems related to agreements based on musyarakah contracts which are based on the principle of justice. This is where the principle of justice plays an important role, especially in standard contracts made by the parties therein. This justice is the most important value that must be reflected in the contract, so as to create an ideal social order.